Meneropong Tradisi: Sanksi Pelanggaran Hukum Adat pada Masyarakat Ulun Lampung - Oktora, Nency Dela (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2023)
The customary law of the people of Lampung in Sukadana District is guided by the Ketaro Adat Lappung which is a book used for the people of Lampung Pepadun. The Lampung Adat Ketaro Manuscript contains customary rules, regarding rules of conduct, marriage, appointment of counterweights, and fines and sanctions (Cepalo 12 (severe sanctions) and Cepalo 80 (ordinary sanctions)) for those who violate customary rules in indigenous peoples. This research is qualitative descriptive research (field research) with inductive thinking. The methods used were interviews, documentation, and observation. Respondents were obtained through purposive sampling techniques. Researchers use language translators in interviews. The implementation of Lampung customary law in relation to customary sanctions has been actualized. If someone violates customary law, he is obliged to report the customary elder regarding his mistake and apologize and repent, then the customary elders consult to decide on a sanction. After the sanction is paid, the pepadun will be upright again. Sanctions for violations, namely compensation for immaterial damages, payment of customary money to those affected, shame cover, apologies, various death sentences, exile (non-active) from society and placing the person outside the legal system. Factors influencing the implementation of Lampung's customary law are its customary law, customary law enforcers, means and facilities to support the implementation of customary law, society (HR), and culture/culture.